A Model to Manage Crude Palm Oil Production System - Inyang, John; Magdalene, anak Andrew Munot; Syed Tarmizi, Bin Syed Shazali; Shirley, Anak Jonathan Tanjong (EDP Sciences, 2019)
This paper reviews key production process for crude palm oil and highlights factors that highly influence the production of crude palm oil. This paper proposes a generic conceptual model for crude palm production process considering these factors. The conceptual model could be modified to consider other factors not included in this paper. The future research would be to construct a simulation model based on the conceptual model proposed in this paper and analyse the effect of these factors on the performance of crude palm oil production system.